2022
DOI: 10.1002/mc.23438
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TFAP2A‐AS1 promotes oral squamous cell carcinoma cell growth and movement via competitively binding miR‐1297 and regulating TFAP2A expression

Abstract: Oral squamous cell carcinoma (OSCC) is an aggressive and common malignancy in the head and neck, characterized by poor prognosis and high incidence. This study aimed to investigate the role of long noncoding RNA TFAP2A-AS1 in OSCC. The competing endogenous RNA network of TFAP2A-AS1 was constructed by bioinformatics analysis. The expressions of miR-1297, TFAP2A-AS1, and TFAP2Awere measured by quantitative reverse transcription-polymerase chain reaction.The correlations of TFAP2A-AS1, miR-1297, and TFAP2A with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Upregulation of TFAP2A has been observed in lung adenocarcinoma and is involved in increased EMT in in vivo and in vitro, as well as increased metastasis of LUAD 22 . In a previous study, we found that TFAP2A can promote the growth of OSCC cells, their transition from epithelial to mesenchymal cells, and their migration and invasion 14 . However, the mechanisms through which TFAP2A affects OSCC development and the molecules with which it interacts are not currently understood.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Upregulation of TFAP2A has been observed in lung adenocarcinoma and is involved in increased EMT in in vivo and in vitro, as well as increased metastasis of LUAD 22 . In a previous study, we found that TFAP2A can promote the growth of OSCC cells, their transition from epithelial to mesenchymal cells, and their migration and invasion 14 . However, the mechanisms through which TFAP2A affects OSCC development and the molecules with which it interacts are not currently understood.…”
Section: Discussionmentioning
confidence: 92%
“…It has been suggested that TFAP2A regulates tectonic 1′s involvement in OSCC, which enhances the invasion, migration, and proliferation of OSCC CAL27 and SCC15 cells 13 . According to our previous study, we found that TFAP2A can promote cell growth, epithelial–mesenchymal transition (EMT), and migration/invasion in OSCC 14 . The target of TFAP2A was, however, not clear in OSCC.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, Linc00467 can regulate miR-1285-3p/TFAP2A expression, thereby facilitating the invasion of head and neck squamous cell carcinoma cells and inhibiting apoptosis ( 13 ). Long-stranded non-coding RNA TFAP2A-AS1 produces oncogenic effects in oral squamous cell carcinoma by regulating the miR-1297/TFAP2A axis ( 34 ). miR-876-5p inhibits breast cancer progression by regulating cell proliferation, migration and invasion in a TFAP2A-dependent manner ( 35 ).…”
Section: Discussionmentioning
confidence: 99%